2019
DOI: 10.1108/lhs-12-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study into the use of Lean Six Sigma to reduce medication errors in the Norwegian public healthcare context

Abstract: Purpose: Medication errors are a significant cause of injury in Norwegian hospitals.The purpose of this study is to explore how Lean Six Sigma has been utilised in the Norwegian public healthcare context to reduce medication errors.Design/Methodology/Approach: A mixed method approach was used to gather data from participants working in the four regions served by the Norway Health Authorities. A survey questionnaire was distributed to 38 healthcare practitioners and semi-structured interviews were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 45 publications
(82 reference statements)
3
41
0
Order By: Relevance
“…Trakulsunti and Antony (2018), implemented Lean and Six Sigma to minimize medication errors in four cases. Antony et al (2019) explored Lean and Six Sigma in the Norwegian public healthcare to decrease medication errors. Ahmed et al (2019) presented the Six Sigma applications within private hospitals in Malaysia.…”
Section: Lean Six Sigma Applications In Healthcarementioning
confidence: 99%
“…Trakulsunti and Antony (2018), implemented Lean and Six Sigma to minimize medication errors in four cases. Antony et al (2019) explored Lean and Six Sigma in the Norwegian public healthcare to decrease medication errors. Ahmed et al (2019) presented the Six Sigma applications within private hospitals in Malaysia.…”
Section: Lean Six Sigma Applications In Healthcarementioning
confidence: 99%
“…The results showed that order entry errors consistently improved by 90% after the deployment of a Six Sigma programme. A recent study has been conducted by Antony, Forthun et al (2019) exploring how Lean Six Sigma has been utilised in the Norwegian public healthcare context to reduce medication errors. This study found that while the implementation of LSS in the Norwegian public healthcare context is still in its infancy, its successful implementation not only reduced medication errors, but also improved staff working performance, patient safety, overall satisfaction and hospital profitability (Ching, 2013;Hintzen et al, 2009).…”
Section: The Application Of Lean Six Sigma In the Reduction Of Medication Errorsmentioning
confidence: 99%
“…The team decided to focus on the medication selection process step. (Antony, Forthun et al, 2019). After the training session, LSS was employed with the researcher acting as consultant to help the participants solve the identified problems.…”
Section: Phase 2: Reflectionmentioning
confidence: 99%
See 2 more Smart Citations